Management, survival, and predictors of mortality among hospitalized heart failure patients at Debre Markos comprehensive specialized hospital, Northwest Ethiopia: Prospective cohort study - Bekalu Kebede (SAGE Publishing, 2021)
Introduction: Heart failure is a major public health problem worldwide. Since heart failure with reduced ejection fraction and preserved ejection fraction are different clinical entities, in-hospital mortality may occur at different rates. This study aimed to assess the management, survival, and predictors of mortality among hospitalized heart failure patients at Debre Markos comprehensive specialized medical ward. Methods: A prospective cohort study was conducted on 228 heart failure patients at Debre Markos Comprehensive Specialized Hospital medical wards. A structured data collection tool was used to collect data. Data were analyzed using SPSS version 21.0. The Kaplan–Meier survival curve was used to investigate if there was a difference in the in-hospital survival between heart failure with a reduced ejection fraction and heart failure with a preserved ejection fraction. Those variables having p -value < 0.05 were considered statistically significant. Results: From the 228 participants, 126 (55.3%) were females with a mean age of 53.32 ± 15.68 years. One hundred thirty-three (58.3%) patients were presented with preserved (⩾50%) level of ejection fraction. The all-cause in-hospital death rate was 12.7%, and the risk of in-hospital mortality was higher in heart failure patients with reduced ejection fraction (7.4% vs 5.3%; p  = 0.005). Current occupation ( p  = 0.041), elevated serum creatinine ( p  = 0.010), reduced ejection fraction ( p  = 0.017), and asthma/chronic obstructive pulmonary disease comorbidity ( p  = 0.002) were the independent predictors of high hospital mortality. Conclusion: The rate of in-hospital mortality among heart failure patients was high. Healthcare providers should provide effective education activities and define disease management strategies for patients with reduced ejection fractions.